Peran Supervisi Akademik dalam Implementasi Kurikulum di Sekolah Dasar: Systematic Literature Review - Pipit Athyana Isniasih; Vita Meitria; Bambang Sumardjoko; Sabar Narimo (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
Academic supervision plays a strategic role in ensuring effective curriculum implementation in primary schools. However, findings on its contribution remain fragmented across various educational contexts. This study aimed to systematically analyze the role of academic supervision in curriculum implementation at the primary school level. The research employed a Systematic Literature Review (SLR) approach based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Literature was collected from Scopus, ERIC, Web of Science, SpringerLink, and Google Scholar using keywords related to academic supervision, instructional supervision, curriculum implementation, and elementary education. A total of 25 empirical studies published between 2022 and 2026 met the inclusion criteria and were analyzed through thematic analysis and narrative synthesis. The findings indicate that academic supervision significantly enhances teacher competence, strengthens instructional planning, and improves curriculum evaluation. Clinical, collaborative, transformational, coaching-based, and digital supervision emerged as the dominant models. The effectiveness of supervision is influenced by principal leadership, collaborative school culture, and policy support, although challenges such as time constraints, administrative burdens, and resistance to change remain prevalent. These findings highlight academic supervision as a critical strategy for improving curriculum implementation and educational quality in primary schools.